2014
DOI: 10.4161/21624011.2014.954460
|View full text |Cite
|
Sign up to set email alerts
|

Cancer chemotherapy agents target intratumoral dendritic cells to potentiate antitumor immunity

Abstract: Cytotoxic drugs capable of killing cancer cells in conjunction with targeted conversion of tumor resident, tolerogenic dendritic cells (DCs) into efficient antigen presenting cells (APCs) are highly complementary therapeutic routes to boost antitumor immunity. Our data suggest that the microtubule-depolymerizing compounds Dolastatin 10 and Ansamitocin P3 may serve as prototypes for a class of agents that display this binary mode of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
(10 reference statements)
0
21
0
Order By: Relevance
“…There is also increasing evidence that combining immunotherapy with selected chemotherapies or antibody‐delivered chemotherapies results in enhanced antitumor activity. Preclinical data indicate that microtubule‐depolymerizing cytotoxic agents can lead to the conversion of tumor‐resident tolerogenic dendritic cells into active antigen‐presenting cells and, in combination with anti–CTLA‐4/PD‐1 therapy, induce innate and adaptive immune responses in patients with breast cancer . On the basis of this rationale, additional patient cohorts were added to this study to evaluate glembatumumab vedotin in combination with the PD‐1–targeted checkpoint inhibitors nivolumab and pembrolizumab, or with the dendritic cell growth factor Flt3 ligand (CDX‐301), in patients with advanced melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…There is also increasing evidence that combining immunotherapy with selected chemotherapies or antibody‐delivered chemotherapies results in enhanced antitumor activity. Preclinical data indicate that microtubule‐depolymerizing cytotoxic agents can lead to the conversion of tumor‐resident tolerogenic dendritic cells into active antigen‐presenting cells and, in combination with anti–CTLA‐4/PD‐1 therapy, induce innate and adaptive immune responses in patients with breast cancer . On the basis of this rationale, additional patient cohorts were added to this study to evaluate glembatumumab vedotin in combination with the PD‐1–targeted checkpoint inhibitors nivolumab and pembrolizumab, or with the dendritic cell growth factor Flt3 ligand (CDX‐301), in patients with advanced melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to DCs and their precursors accumulating in the tumor microenvironment and exacerbate the immunosuppressive action of the tumor. Therefore, intervening and converting the immature DCs to mature antigen‐presenting cells is an important target for immune‐therapy based cancer treatment . MT‐destabilizing agents including ansamitocin P3, dolastatin, and antibody‐drug conjugates containing dolastatin‐10 analogs have been shown to induce functional DC maturation and activation, and also increase the capacity of priming antigen‐specific CD4+ and CD8+ T cells .…”
Section: Mt‐targeting Agents’ Potentiation Of Immune Response and Impmentioning
confidence: 99%
“…MT‐destabilizing agents including ansamitocin P3, dolastatin, and antibody‐drug conjugates containing dolastatin‐10 analogs have been shown to induce functional DC maturation and activation, and also increase the capacity of priming antigen‐specific CD4+ and CD8+ T cells . It has also been reported that other classes of MT‐destabilizing agents can activate DCs, unlike MT stabilizing agents which only invoked minimal activation in murine cells and caused no observed effect in DCs . Another group also investigated the effects of MT‐destabilizing agents on DC maturation and T‐cell activation in relation to immunogenic tumor cell death.…”
Section: Mt‐targeting Agents’ Potentiation Of Immune Response and Impmentioning
confidence: 99%
See 2 more Smart Citations